Strategi Promosi Dan Rotasi Kerja Pegawai Pada Sekretariat Dprd Kabupaten Tanah Bumbu - Trisylvana Azwari; Novi Shintia; Agus Pebrianto (BIMA: Jurnal Bisnis dan Manajemen, 2022)
The problem facing the Secretariat of the DPRD Tanah Bumbu Regency is that it is currently a mistake to put employees in a position that is not their expertise. The purpose of this study that the constituents did 1) To find out the strategy of promotion and rotation of work employees related to the promotion and rotation of employee work at the Secretariat of the DPRD tanah Bumbu regency. 2) To find out the right promotion and rotation strategies related to the promotion and rotation of employee work at the Secretariat of the DPRD tanah Bumbu regency. The method used in conducting this Final Task research is Descriptive, where the constituent will describe and explain the events regarding employee work placement including promotion and rotation of work in the relevant agency. The data sources used are primary data and secondary data. The variables used in this study are free variables i.e. employee work placement and bound variables that are strategies. The data collection techniques that the constituents do are questionnaires and documentation. From the results of this study it can be concluded that the placement of employees in the Secretariat of the DPRD tanah Bumbu regency can be said to be good in its application. It can be seen in the promotion of employees that employee promotion is good in its activities. Similarly, in the rotation / mutation activities of employees, as well as rotation / mutation indicators in the Secretariat of the DprD tanah Bumbu regency can be said to be good so as to realize the appropriate placement of employees.